ASSESSMENT OF THE INPUTS ASPECT OF THE QUALITY OF HOSPITAL CARE IN TIANJIN FIRST CENTRAL HOSPITAL (TFCH), TIANJIN, CHINA BY INPATIENTS - Khan, Noor Ahmad; Ramie, Hamdija; Bing, Liu; Jianguo, Li (Journal of Ayub Medical College Abbottabad, 1998)
This descriptive cross sectional study on the users' assessment of the structural aspect of quality' of care has been conducted from 4th May to 6h June ]996, in TFC hospital, Tianjin. The objective was to assess the structural aspect of quality of care by users' point of view and to identify possible areas of intervention for its improvement. Stratified multistage sampling was used and face to face interviews with 181 users in In-Patients Departments (IPD) were conducted. Using Donabedian 's classification of quality the structural/ inputs aspect of quality was assessed through the dependent and independent variables of quality. The results revealed that 82 % of the users were within 20hn distance from the hospital. A total of 74% term reaching to the hospital as convenient and expenditure not so high (71.8%). An overwhelming majority term the hospitalization as easy (90.4%), cleanliness good (94.9 %) and drugs available (92.7%). A total of 93.2% term the services received worth the money paid. Key words: - Users, Inpatients, Quality Assessment, Hospital Care.